PANDANGAN AL-QUR’AN MENGENAI BANK ASI - Shofiatul Jannah, Shofiatul Jannah (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2020)
This research aims to determine the views of the Qur'an regarding the legal status of ASI banks. Therefore, this study is expected to provide answers to the controversy that occurred. This research method is a library research method, namely a method of reviewing written data both books, literature and notes and reports that have a correlation with the discussion. This research uses descriptive-analytic method, namely using existing sources, then describing it, then analyzing how